Role of bone scan in addition to CT in patients with breast cancer selected for systemic staging. Issue 7 (23rd March 2016) - McCartan, D P; Prichard, R S; MacDermott, R J; Rothwell, J; Geraghty, J; Evoy, D; Quinn, C M; Skehan, S J; O'Doherty, A; McDermott, E W
Abstract: Background: The majority of women with breast cancer present with localized disease. The optimal strategy for identifying patients with metastatic disease at diagnosis remains unclear. The aim of this study was to evaluate the additional diagnostic yield from isotope bone scanning when added to CT staging of the thorax, abdomen and pelvis (CT-TAP) in patients with newly diagnosed breast cancer. Methods: All patients diagnosed with breast cancer who underwent staging CT-TAP and bone scan between 2011 and 2013 were identified from a prospective database of a tertiary referral breast cancer centre that provides a symptomatic and population-based screening breast service. Criteria for staging included: biopsy-proven axillary nodal metastases; planned neoadjuvant chemotherapy or mastectomy; locally advanced or inflammatory breast cancer and symptoms suggestive of metastases. Results: A total of 631 patients underwent staging by CT-TAP and bone scan. Of these, 69 patients (10·9 per cent) had distant metastasis at presentation, with disease confined to a single organ in 49 patients (71 per cent) and 20 (29 per cent) having metastatic deposits in multiple organs. Bone metastasis was the most common site; 39 of 49 patients had bone metastasis alone and 12 had a single isolated metastatic deposit. All but two of these were to the axial skeleton. No preoperative histological factors identified a cohort of patients at risk of metastatic disease. Omission of the bone scan in systemic staging would have resulted in a false-negative rate of 0·8 per cent. Conclusion: For patients diagnosed with breast cancer, CT-TAP is a satisfactory stand-alone investigation for systemic staging. Abstract : Little added value